2013
DOI: 10.1007/s00276-013-1225-y
|View full text |Cite
|
Sign up to set email alerts
|

Geometry of the Clavicle and Reliability of Measurement using PACS

Abstract: The geometry of the clavicle is influenced by sex and side. Use of PACS as a measurement tool is reliable. Data from this study will be useful for pre-contouring plate or improving future designs of the anatomical plate of the clavicle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…The length before fracture was calculated by adding the length of the affected clavicle to the amount of measured fracture overlap, as we did not have information of the length of the clavicle prior to fracture. The contralateral clavicle was not used as a reference, because of possible pre-existent clavicular asymmetry ( Cunningham et al 2013 , Wisanuyotin et al 2013 ). To calculate this relative shortening, the initial anteroposterior (AP) trauma radiograph was used—as well as an AP panorama radiograph comprising both clavicles that was acquired during the study visit (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…The length before fracture was calculated by adding the length of the affected clavicle to the amount of measured fracture overlap, as we did not have information of the length of the clavicle prior to fracture. The contralateral clavicle was not used as a reference, because of possible pre-existent clavicular asymmetry ( Cunningham et al 2013 , Wisanuyotin et al 2013 ). To calculate this relative shortening, the initial anteroposterior (AP) trauma radiograph was used—as well as an AP panorama radiograph comprising both clavicles that was acquired during the study visit (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…We observed significant differences between genders in the anatomy around the AC joint, which we believe to be a clinically relevant observation. Similarly, Wisanuyotin et al 20) also reported that the anatomy of the clavicle is significantly different between genders. In the present study, the female gender has a significantly larger AC angle (13.8° vs. 19.8°), and thinner distal clavicle (12.2 mm vs. 10.9 mm) and acromion (8.7 mm vs. 7.7 mm) as compared to the male gender.…”
Section: Discussionmentioning
confidence: 90%
“…2,44,54,57 The radiographs were viewed on a picture archiving and communication system, which allowed accurate distance measurements. 15,59 The natural variation in clavicle length was taken into consideration in interpreting results. 3,59 Statistics Statistical analysis was performed with IBM SPSS Statistics version 22 (IBM Corp., Armonk, NY, USA).…”
Section: Patient-oriented Outcomesmentioning
confidence: 99%
“…15,59 The natural variation in clavicle length was taken into consideration in interpreting results. 3,59 Statistics Statistical analysis was performed with IBM SPSS Statistics version 22 (IBM Corp., Armonk, NY, USA). Percentage, frequency distribution, mean, median, and standard deviation were used to describe the characteristics of variables.…”
Section: Patient-oriented Outcomesmentioning
confidence: 99%